Research on the effects of temperature, salinity and nutrition to the growth of the Betaphycus gelatinus (Esper) Doty - Trung, Vo Thanh; Huynh, Tran Van; Duc, Tran Mai; Nghia, Le Trong; Hung, Pham Duc (Academia Journal of Biology, 2021)
Betaphycus gelatinus (Esper) Doty (BG) is a red seaweed that has been used as a food and a research material. Thus, the study on factors affecting the growth and development of BG is necessary. The present results show that the good growth conditions of BG are 27 oC, 30‰ of salinity, and add PES or Nitrate-phosphate medium. This research has important scientific significance in preserving and restoring rare and valuable commercial seaweed varieties.